Resource Warehouses; a Distributed Information Warehouse Infrastructure - Khoury, Simon; Kropf, Peter; Babin, Gilbert (My University, 2002)
This paper presents work related to the design of distributed systems, which is useful for emerging Internet applications. We propose algorithms for searching and managing distributed information about resources and services using locally available warehouses. The concept of warehouses has been introduced in the Web Operating System (WOS) (Kropf 1999). Warehouses have the ability to decide which information should be stored, replaced or removed without any intervention of the user. We present a tree structure for WOS warehouses, an attribute/value scheme used for describing resources, and the algorithms to look up information about resources. Among other things, warehouses take into account the capacity limitations of the devices that the WOS is using. Moreover, in order to share locally available information, WOS warehouses need to communicate with each other. We present an approach which allows for profitable exchange of information between the various warehouses. The advantage of our ap- proach is the use of a simple method to describe what is be- ing looked for (i.e., the intent), instead of specifying where to find it (i.e., the extent). We have implemented our warehouse structure in Java taking advantage of its portability.
Keywords: Distributed Systems; Communication Protocol; Middleware; Resource Management; Web Operating System (WOS); Resource localization